Hubungan Desain Interior Terhadap Kenyamanan Pemustaka Di Perpustakaan Umum Kabupaten Solok - Zulfa Firdha Nita; Cut Afrina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This research develops three main issues, namely how is the interior design condition in the Solok Regency Public Library, what is the comfort level of the users in the Solok Regency Public Library, is there any influence of the interior design of the library on the comfort level of the users in the Solok Regency Public Library. The purpose of this study was to determine the effect of the relationship between library interior design and the comfort level of users, the interior design includes layout, lighting, and temperature, with partial and simultaneous research. The type of research that researchers use is the type of associative research or relationship (influence) using a quantitative approach. This research was conducted at the Solok District Public Library. The population used in this study were users who visited the Solok District Public Library using the incidental sampling technique. The number of samples taken by the researchers totaled 87 samples. Data collection using questionnaires and questionnaires. Validity test, reliability test and product moment correlation test using IMB SPSS v20 program. The results of the study can be concluded that the r value of 0.667 is categorized as moderate and positive, meaning that there is a relationship between the interior design of the library and the comfort level of users and the results of the simple regression equation, Y = 79.415 + 0.659X. The two levels of influence between variable X and variable Y are 44%. So this can be interpreted that 56% of interior design is influenced by factors other than user comfort. With a regression coefficient b = 0.667 indicating the magnitude of the addition of the user's comfort level for interior design assessment. The results of hypothesis testing are done by t test with an error of 5%, then t table = 1.262 is obtained. If t count = 2.529 > t table = 1.262, then Ho is rejected and Ha is accepted, which shows that there is an influence of interior design on the comfort of users in the public library of Solok Regency.